Injuries among Portuguese kitesurfers: The most affected body regions. A pilot study - Silva,Bruno (2015)
Aquatic sports keep rising in popularity. Kitesurfing is a high-risk sport that combines aspects of several water sports. Kitesurfing is a relatively new water sport, and the understanding of the injuries due to its practice has not yet been largely investigated. The purpose of this study is to investigate the most common types and causes of injuries among Portuguese kitesurfers. The data was collected using a retrospective 12 months web-based questionnaire. A total of 87 kitesurfers, mostly from the North, showed that 75.9% have a kitesurfing initiation course and 56.3% use protective equipment. A total of 60.9% has been injured in the 12 months period, being the knee and the lumbar spine the most common body injury. A reasonable number of injuries occurred while performing a landing or a maneuver, being 53.9% of the injuries reported as a new injury. This 12 months retrospective study supports earlier studies and provides basis knowledge about the incidence of Portuguese kitesurfers injuries. The data support the benefits of physical fitness (p< 0.05) in injuries prevention.